2020
DOI: 10.1021/acscatal.0c01604
|View full text |Cite
|
Sign up to set email alerts
|

CuxIr1–x Nanoalloy Catalysts Achieve Near 100% Selectivity for Aqueous Nitrite Reduction to NH3

Abstract: Nitrite (NO2 –) is an abundant contaminant in nature that threatens human health. A catalytic process that converts NO2 – to less harmful products has been proven to be an effective strategy for NO2 – removal. Most previous studies, however, targeted selectivity toward N2 using Pd catalysts, which severely limits the potential for the recovery of value-added byproducts from the catalytic process. Here, we report experimental and theoretical evidence that both Ir and Cu x Ir(100–x) nanoparticles possess near 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 52 publications
(121 reference statements)
1
52
0
Order By: Relevance
“…It decreases from near 90% to almost zero with applied potential from −1.0 V/RE to −0.40 V/RE, respectively. This decrease corresponds to smaller amounts of reactive hydrogen on the catalyst surface, and is consistent with conventional catalytic studies that found less ammonium is formed when the hydrogen supply is limited. ,,, This has been attributed to higher coverage of nitrogen species on the catalyst surface at low hydrogen levels, and the greater chance for N–N pairing to occur and form dinitrogen. ,,, Selectivity for dinitrogen is important in water treatment plants to avoid producing and releasing toxic ammonium to the water distribution system or the environment.…”
Section: Resultssupporting
confidence: 76%
“…It decreases from near 90% to almost zero with applied potential from −1.0 V/RE to −0.40 V/RE, respectively. This decrease corresponds to smaller amounts of reactive hydrogen on the catalyst surface, and is consistent with conventional catalytic studies that found less ammonium is formed when the hydrogen supply is limited. ,,, This has been attributed to higher coverage of nitrogen species on the catalyst surface at low hydrogen levels, and the greater chance for N–N pairing to occur and form dinitrogen. ,,, Selectivity for dinitrogen is important in water treatment plants to avoid producing and releasing toxic ammonium to the water distribution system or the environment.…”
Section: Resultssupporting
confidence: 76%
“…e ., bridge and hollow sites) for the most stable H* co-adsorption at different monometallic surfaces. Co-adsorbed hydrogen atoms are preferably adsorbed on the hollow sites of Au, Ag, Cu, Ni, Pd, and Rh(111) while on the bridge sites of Ir and Pt(111) due to their broader 5d band. , …”
Section: Resultsmentioning
confidence: 99%
“…Co-adsorbed hydrogen atoms are preferably adsorbed on the hollow sites of Au, Ag, Cu, Ni, Pd, and Rh(111) while on the bridge sites of Ir and Pt(111) due to their broader 5d band. 63,64 Figure 3 65 The overall energy barrier of hydrogen associative desorption (defined as the highest value of the free energy diagram of hydrogen desorption) follows the order: Au < Ir < Ag < Pt < Cu < Rh < Ni < Pd. The overall energy barriers of the surfaces with Mechanism 2 are higher than those with Mechanism 1.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 This is not only due to the less consumption of noble metals but also their potential unique catalytic properties, which are absent in their monometallic counterparts. 3,4 In particular, bimetallic nanoparticle (NP) catalysts containing Au (e.g., Ni-Au) show various intriguing catalytic properties, such as excellent CO 2 hydrogenation activity, superior activity and robust durability for hydrogen evolution reaction, great sensitivity on non-enzymatic glucose sensing and high efficiency in automotive exhaust gas purification. [5][6][7][8] Continuous optimization of the bimetallic catalysts is achieved through controlling its morphology and structure, regulating the content of two distinct metals, reducing the coordination number of surface atoms and utilizing suitable supports to enable unique synergies.…”
Section: Introductionmentioning
confidence: 99%